The influence of prosthetic material on implant and prosthetic survival of implant-supported fixed complete dentures: a systematic review and meta-analysis. Issue 3 (July 2019) - Bagegni, Aimen; Abou-Ayash, Samir; Rücker, Gerta; Algarny, Ahmad; Att, Wael
Abstract: Purpose: Evaluating the impact of the prosthetic material on implant- and prosthetic survival of implant-supported fixed complete dentures. Study selection: Electronic and hand searches were conducted according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) to identify clinical studies including at least 10 patients restored with implant-supported dentures. The primary outcome was to evaluate the implant survival rate according to the applied restorative materials. The prosthetic survival rate was evaluated as secondary outcomes. Results: Forty-one of 2254 studies were ﬁnally selected. A statistically significant difference (p = 0.0337) was found between implant survival rates in the main restorative groups (metal-ceramic:97%(95%CI [0.96;0.98]), all-ceramic:99%(95%CI [0.98;1.00]), metal-resin:97%(95%CI [0.96;0.98])). Prosthetic survival rates were: (metal-ceramic:95%(95%CI [0.89;0.97]), all-ceramic:97%(95%CI [0.92;0.99]), metal-resin:97%(95%CI [0.95;0.98]), with no statistically significant difference (p = 0.3796) between the groups. Chipping incidence rates were as follows: metal-ceramic:8%(95%CI[0.03;0.20]), all-ceramic:15%(95%CI [0.06;0.32]), and metal-resin:22%(95%CI [0.13;0.33]). Five types of exact restorative materials were identified (porcelain-fused-to-non-precious alloy, porcelain-fused-to-zirconia, precious-metal-acrylic-resin, non-precious-metal-acrylic resin, and PMMA). Again, implant survival rates were statistically significantly influenced by the applied restorative materials (p = 0.0126), whereas, no significant differences were reported regarding prosthetic survival rate. Conclusions: Prosthetic material selection seems to have no clinically relevant influence on implant- and prosthetic survival rate in implant-supported fixed complete dentures. Due to the high chipping rate, quantifying prosthetic survival alone does not seem to be a reliable tool for evaluating the outcome of the restorations and providing recommendations. These results, along with the obvious lack of evidence, suggest that clinicians must exercise caution whenever porcelain-fused-to-zirconia or metal-resin restorations are considered.